Increased risk of osteoporosis in depressive patients with eractile dysfunction: a cross-sectional study from Malaysia - Fata Nahas, Abdul Rahman; Syed Sulaiman, Syed Azhar (Medknow Publications, 2017)
Background: Depression imposes numerous changes on depressive men, promoting for low bone mineral density (BMD) and erectile dysfunction (ED), yet no published data on exploring the possible association between these two disorders among depressive men. We therefore investigated whether low BMD is associated with ED among depressive men and highlighted the possible mutual underlying factors that might give rise to these two disorders in this specific group of patients. Materials and Methods: In this cross-sectional study, 119 depressive men were recruited and their sociodemographic and clinical characteristics were obtained. Erectile function was evaluated using the 5-item International Index of Erectile Function. All patients received a calcaneal BMD scanning. Chi-square test was conducted to determine if a significant association exists between ED and low BMD. Results: Of the study participants, ninety patients reported ED, while 29 patients reported no ED. Within the ED group, there was a significantly higher proportion of patients with low BMD compared to the non-ED group (85.6% vs. 62.1%, P = 0.006). In addition, among younger participants (i.e., aged < 50 years old), the difference in T-score between ED patients (Md =-2.2, n = 41) and non-ED patients (Md =-1.3, n = 20) was significant (P = 0.001); but held no significance among older participants. Conclusions: While our findings are considered prefatory, we reported that low BMD was significantly associated with ED in depressive men and that only among young depressive patients, BMD was significantly lower in ED patients compared to non-ED patients. More research investigating these findings and the possible underlying mechanisms for such association are warranted.